Identification and expression of two types of chicken GnRH-II genes in mature hard-lipped barb, Osteochilus hasselti - N. A. PRAYOGO; G. E. WIJAYANTI; I. SULISTYO; P. SUKARDI (Society for Indonesian Biodiversity, 2016)
Abstract. Prayogo NA, Wijayanti GE, Sulistyo I. Sukardi P. 2016. Identification and expression of two types of chicken GnRH-II genes in mature hard-lipped barb, Osteochilus hasselti. Biodiversitas 17: xxx. Gonadotropin-releasing hormone (GnRH) is synthesized in the brain and acts in the anterior pituitary to stimulate the release of gonadotropins in fishes as well as in other vertebrates. Genomic DNAs and cDNAs of two chicken-type GnRH-II genes of hard-lipped barb, namely cGnRH-II type 1 and type 2, were cloned. The length of cloned genomic DNA of cGnRH-II type 1 was 580 bp and cDNA was 206 bp. The length of cloned genomic DNA of cGnRH-II type 2 was 570 bp and cDNA was 196 bp. The cGnRH-II type 1 and type 2 cDNAs encode precursors of 68 and 63 amino acids, respectively. Those precursors consist of a signal peptide, cGnRH-II decapeptide and a GnRH-associated peptide (GAP) linked by a Gly-Lys-Argproteolytic site. Using quantitative Real Time-PCR, expression levels of these two cGnRH-II genes were detected in the brain, liver and gonad of hard-lipped barb. Expression of the GnRH-II type 1 gene was found only in the brain and liver, on the other hand, expression of the cGnRH-II type 2 gene was found in the gonad, in addition to the brain and liver. The expression of the cGnRH-II genes outside the brain suggested that cGnRH-II might act as an autocrine or paracrine regulator.